Multi-scale effects of stretch on peripheral nerves - Bianchi, F (2018)
Peripheral nerve injury, leading to loss of motor and sensory function, is a burdensome consequence of trauma, surgery or chronic conditions. Mechanical forces play a substantial role in the onset of injury, and affect peripheral nerves at varying length scales, from tissues to individual cells. A multi-scale approach is therefore required to understand how supraphysiological levels of deformation at the nerve level can affect function at the single-cell level. The aim of this project was to investigate the multi-scale effects of stretch at the tissue and cell length scales, through the development of experimental in vitro models of peripheral nerve injury. At the macroscopic (tissue) level, the aim was to quantify the partitioning of strain between nerve and neurons, by measuring microscopic strains during in situ extension of peripheral nerves. At the microscopic level, the aim was to quantify the effects of cell strain and mechanical properties on the electrophysiolgical activity of neurons. At the whole tissue level, the transfer of tissue-scale strain to the micro-scale was investigated by X-ray diffraction and MPM imaging during tensile loading. Axially, the strain in peripheral nerves was shown to partly transfer to the axially aligned collagen fibres ensheathing the nerve core. The transfer of axial strain to axons was evaluated by using Nodes of Ranvier as markers for digital image correlation, providing a direct relationship between tissue and cell scale mechanics. Radially, a small fraction of the induced compression was transferred to the myelin sheath, suggesting a high stiffness and a potential protective role. Plastic damage in collagenous tissue was examined by evaluating changes in micro-scale mechanical properties, showing distinct behaviours at the collagen fibril and molecule levels. These results establish a mechanical link between nerve extension and microscopic deformations that affect individual cells within the tissue. In order to investigate the effect at the microscopic cell scale, novel in vitro models were developed. A cell-stretching device was designed to apply uniaxial strain to cultured neurons, and simultaneously allow electrophysiological measurements. Human induced pluripotent cells were differentiated to functional motor neurons, and the effect of uniaxial strain was evaluated by measuring the alterations in network and single-cell electrophysiology. Calcium flux imaging showed an immediate decrease in spontaneous network activity with applied strain, and whole-cell patch clamping was used to show changes in ion channel dynamics. C-Laurdan imaging showed a linear fluidisation effect of stretch on the lipid packing of neural membranes, suggesting that the mechanical state of the membrane is changed during straining. Altering the cell membrane's mechanical properties by increasing cholesterol was shown to reduce membrane fluidisation and significantly mitigate the loss of spontaneous activity due to strain. The development of multi-scale mechanical models can help tissue engineers and clinicians understand how trauma directly affects the functionality of cells. In peripheral nerves that are continuously exposed to mechanical forces, a better understanding of how strain is transferred from the macro-scale to the micro-scale and how this affects neuron activity will help advance preventive and treatment strategies, as well as inform and validate computational models and the design of artificial nerve tissue replacements.